Symposium: Design and Disaster: Higher Education Research Responds to Hurricane Katrina: Equity Planning in Post-Hurricane Katrina New Orleans: Lessons from the Ninth Ward - Reardon, Kenneth M.; Ionescu-Heroiu, Marcel; Rumbach, Andrew J. (2012)
This article describes how grassroots activists and community leaders representing poor and working class residents of New Orleans, together with planning students and faculty from three research universities, overcame racial, class, and cultural barriers to collaboration to create and promote a comprehensive Hurricane Katrina recovery plan for the neighborhoods that make up the city's Ninth Ward.